Early Administration of Rifampicin Does Not Induce Increased Resistance in Septic Two-Stage Revision Knee and Hip Arthroplasty - Leonard Grünwald; Benedikt Paul Blersch; Bernd Fink (Antibiotics)
Background/Objectives: Periprosthetic joint infection (PJI) is a severe complication that follows arthroplasty and occurs in approximately 2% of all cases. One of several cornerstones of therapy is an optimized antibiotic regimen. Early administration of rifampicin—together with a combination of an antibiotic to which the specific microorganism is susceptible—accompanying a two-stage revision surgery, remained controversial due to the potential risk of emerging resistance. However, the exact time to start rifampicin treatment often remains unclear and might be crucial in the treatment regimen. Methods: In a retrospective study design, a total of 212 patients receiving a two-stage revision surgery after a diagnosis of PJI (60.8% THA, 39.2% TKA) received an individual rifampicin combination therapy after initial debridement and removal of all foreign material, starting rifampicin on the second day postoperatively. Results: At the time of spacer explantation, two patients had developed rifampicin resistance (0.9%). At follow-up (M = 55.4 ± 21.8 months) after reimplantation, three patients had developed rifampicin resistance (1.4%). Concerning the development of reinfection, in general, in the study group and the necessity for further treatment, a total of 25 patients showed signs of reinfection (11.8%). Conclusions: Only 0.9% after the first stage and 1.4% at follow-up after the second stage of all 212 patients with accompanying long-term rifampicin combination therapy developed a rifampicin resistance. Therefore, rifampicin administration could be started on the second postoperative day when sufficient concentrations of the accompanying antibiotics can be expected.